Role of Department of Cottage and Small Industry in Women Enterprise Development Programme in Nepal - Singdel, Minu (PYC Nepal Journal of Management, 2015)
Women entrepreneurship development (WED) programme is essential for encouraging women to undertake economic activities. Experience shows that there are large numbers of women capable of and willing to participate in economic activities but there is a lack of integrated and need-based WED programme. This article looks at the role playedby Department of Cottage and Small Industries (DCSI) in development of women entrepreneurship in Nepal. The article examines the data published by DCSI and tries to analyze the trend of women entrepreneur taking various business related training from DCSI.